DEVELOPMENT AND VALIDATION OF AN INVENTORY TO EVALUATE THE ENTREPRENEURSHIP CURRICULUM IN COMMUNITY COLLEGES - Muhaimin Roji; Nor Hasnida Che Md Ghazali; Norfishah Mat Rabi; Norwaliza Abdul Wahab, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In order to evaluate the implementation of a program, one needs a valid, reliable and practical instrument. The purpose of this study is to develop and assess the validity and reliability of an inventory which is used to evaluate the implementation of entrepreneurship curriculum in community colleges around Selangor and Perak. The inventory is developed by the researcher, and it is in the form of a questionnaire with a 5-Likert scale. The conceptual framework of this study follows the CIPP Model developed by Daniel Stufflebeam. The initial instrument consists of 76 items which are divided into four main constructs – context, input, process, and product evaluation dimension. The sample of this pilot study were 50 students who are studying in semester three and above in the community colleges in Selangor and Perak. The content validity is assessed by the experts, and the construct validity is measured by Exploratory Factor Analysis. The reliability of the instrument is measured using internal consistency reliability, which is alpha coefficient reliability or Cronbach Alpha. Results of Exploratory Factor Analysis suggest that 16 items need to be removed due to their non-dimensionality as they have more or less equal loadings on several factors. The instrument developed yielded high values of internal consistency as reflected by the Cronbach alpha values after deleting another 2 items. Thus, the final draft of the instrument contains 58 items which are valid and reliable. Even though the validity and reliability of the instrument are within the acceptable range, more data need to be gathered using a bigger sample size, and further analysis using confirmatory factor analysis could be used to explore deeper into the psychometric characteristics of the items before the instrument can be finalized.